UV-Visible Spectrophotometric as a Prospective Tool in Neonatal Sepsis - Eko Suhartono; Ari Yunanto; Edi Hartoyo; Nia Kania; Adelia Anggraini Utama; Ratih Kumala Sari; Niarsari Anugrahing Putri; Iskandar Thalib (The Indonesian Biomedical Journal, 2018)
BACKGROUND: This study was aimed to employ the UV-Visible (UV-Vis) spectrophotometry techniques to detect the changes in the blood of neonatal sepsis (NS) subject for a deeper understanding in the pathomechanism of NS.METHODS: The cross-sectional study was conducted from February to May 2017 in the Neonatology Division, Department of Pediatric, Ulin General Hospital/Faculty of Medicine, Lambung Mangkurat University, Banjarmasin, South Kalimantan, Indonesia. Blood specimens were taken from newborns, of which 15 each of newborns at risk of sepsis and without risk of sepsis. Data were analyzed by using Mann-Whitney U test.RESULTS: The result of this study suggested that there is a significant difference in the average of absorbance ratio parameter using UV-Vis spectrophotometric methods on the case group compared to the control group. Also, there is a significant difference between advanced oxidation protein products (AOPPs) and thiocyanate (SCN) level in newborn at risk of sepsis.CONCLUSION: The present study demonstrated there were significant differences between the average of absorbance ratio parameter for protein and oxy-hemoglobin region using UV-Vis spectrophotometric methods in healthy subjects and newborn at risk of sepsis.KEYWORDS: spectrophotometric, neonatal sepsis, oxidative stress